Kontribusi Media Peraturan Permainan Dan Sinyal Wasit Berbasis Adobe Flash Dalam Mengedukasi Siswa Ekstrakurikuler Futsal - Nugroho, Mahir Dwi; Widiyanto, Widiyanto (Faculty of Sport and Health Sciences, 2021)
This study aims to determine the effect of using media based on adobe in understanding laws of the game and referee signals on futsal media based on adobe flash. This study used an experimental approach with a one-group pretest-posttest design or experiment in the pre-experimental design type. The results showed an increase in the understanding of extracurricular students with the following results: The results of the pretest score of 56.20 and the mean posttest score of 73.33 based on the results of the pretest and posttest showed an increase with a score difference of 17.13 while the students perceptions of media quality were categorized as criteria